ANALISIS ANGGARAN DANA DESA TERHADAP PEMBANGUNAN INFRASTRUKTUR DAN PEMBERDAYAAN MASYARAKAT (Studi:Penggunaan Anggaran Dana Desa Di Oyah Kiri Kec.menukung Kab.Melawi Prov.Kalbar) - Safitri, Bella; Ahmad Pabulo, Azfa Mutiara (JURNAL ILMIAH EDUNOMIKA, 2024)
Finding out whether the Village Fund in Oyah Kiri Village encourages community empowerment and impacts the development of village infrastructure is the goal of this study. Interviews, participant observation, document analysis, and literature reviews are all part of the data gathering process in this qualitative descriptive research.The findings indicate that Oyah Kiri Village covers an area of 2,960 hectares, characterized by hilly terrain, highlands, rivers, and wetlands that serve as agricultural land. The climate in Oyah Kiri is tropical. Most residents engage in farming, fishing, and various jobs. The village has a population of 833 individuals, consisting of 187 family units (KK), divided into six Neighborhood Associations (RT). The demographic breakdown shows 406 males and 427 females, with religious affiliations comprising 179 Muslims, 211 Christians, and 443 Catholics. Keywords : Village Fund, Infrastructure Development, Community Empowerment.